Surgical Management and Post-Operative Outcomes of Urinary Outflow Obstruction: Experience of 50 Cases in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Management of urinary outflow obstruction is very crucial.Objective: The purpose of the present study was to see the different management of urinary outflow obstruction with their post-operative outcomes.Methodology: This non-randomized clinical trial was conducted in the Department of Surgery at Rajshahi Medical College, Rajshahi, Bangladesh from September 1994 to December 1995 for a period of one year and three months. All the patients who were presented with bladder outflow obstruction and were admitted in the general surgical unit of the hospital were taken as study population. These patients were surgically managed in different procedures. The follow up was done to record the post-operative surgical outcomes.Result: A total number of 50 patients were recruited for this study. Benign enlargement of prostate was found in 13 cases of which 11(22.0%) cases were managed by suprapubic transvesical prostatectomy. Impacted urethral stone was found in 13 cases of which 4(8.0%) cases were managed by urethro-lithotomy followed by repair of urethra and indwelling catheter. Stricture urethra was found in 11 cases and all cases (100.0%) cases were managed by intermittent dilatation under general anesthesia. In 7 cases of rupture urethra, initially all patients were managed by suprabpublic cystostomy which was 7(14.0%) cases in number. All the 3 cases of carcinoma prostate were managed by prostatectomy and radiotherapy plus hormone therapy. A total number of 16 patients were managed by prostatectomy of which 1(2.0%) case was developed immediate postoperative hemorrhage which was managed by blood transfusion and continuous irrigation with normal saline. One patient developed postoperative clot retention due to blockage of Foley’s catheter, two patients developed postoperative incontinence, immediately after removal of the catheter. Out of 11 patients of impacted urethral stone, one developed urethral fistula and one developed UTI. Recurrent stricture urethra occurred in 3 patients. Seven patients with rupture urethra, 3 developed stricture urethra and 3 developed stricture urethra.Conclusion: In conclusion different surgical procedure are employed during the management of urinary outflow obstruction and immediate postoperative hemorrhage, postoperative clot retention, postoperative incontinence, urethral fistula, UTI and recurrent stricture urethra are the most common complication after surgical management of urinary outflow obstruction patients.Journal of National Institute of Neurosciences Bangladesh, 2017;3(2): 84-88